2016
DOI: 10.1177/0954406216684364
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary analysis of nonlinear rotating shafts passing through critical speed excited by a nonideal energy source

Abstract: In this paper, the effect of nonlinearity on vibration of a rotating shaft passing through critical speed excited by nonideal energy source is investigated. Here, the interaction between a nonlinear gyroscopic continuous system (i.e. rotating shaft) and the energy source is considered. In the shaft model, the rotary inertia and gyroscopic effects are included, but shear deformation is neglected. The nonlinearity is due to large deflection of the shaft. Firstly, nonlinear equations of motion governing the flexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…It is observed that in the case of larger driving torque, the response amplitude is smaller. In this case, the angular acceleration is large and the system does not enough time to take the maximum response . On the other hand, when the driving torque is small, amplitude increases and this condition holds up to the steady‐state situation.…”
Section: Numerical Examplesmentioning
confidence: 98%
See 4 more Smart Citations
“…It is observed that in the case of larger driving torque, the response amplitude is smaller. In this case, the angular acceleration is large and the system does not enough time to take the maximum response . On the other hand, when the driving torque is small, amplitude increases and this condition holds up to the steady‐state situation.…”
Section: Numerical Examplesmentioning
confidence: 98%
“…Angular velocity vector ω of an arbitrary shaft cross section is acquired from Euler's angle as leftω=ω1e1+ω2e2+ω3e3=(trueβ̇+trueφ̇trueψ̇prefixsinθ)e1left2em+0.33em(trueψ̇prefixsin(β+φ)prefixcosθ+trueθ̇prefixcosβ)e2+(trueψ̇prefixcos(β+φ)prefixcosθtrueθ̇prefixsinβ)e3where the symbol (·) denotes the derivative with respect to time. Position and velocity of an arbitrary point (x,y,z) on the deformed shaft can be calculated as leftboldR=(x+u)eX+v0.16emeY+w0.16emeZ+(ay+y)e2+(az+z)e3lefttrueṘ=trueu̇0.16emeX+truev̇0.16emeY+trueẇ0.16emeZ+ω×[(ay+y)e2+…”
Section: Equations Of Motion Of a Nonlinear Composite Shaftmentioning
confidence: 99%
See 3 more Smart Citations